DIAGENETIC CHARACTERIZATION OF DINOSAUR REMAINS THROUGH HISTOLOGY IN FLUVIAL CONTEXTS FROM THE UPPER CRETACEOUS OF THE LONCOCHE FORMATION, MENDOZA, ARGENTINA (Ameghiniana, 2019)
Histological and diagenetic features of sauropod and theropod bones from the late Cretaceous Loncoche Formation of southern Mendoza, Argentina were analyzed to elucidate the degree and type of taphonomic alteration in relation to their depositional environment. The histological thin sections reveal a predominance of fibrolamellar bone tissue in the sauropod suggesting an overall fast bone growth, contrarythe presence of parallel-fibered bone tissue that suggests a slow-down growth in the theropod. However, the existence of lines of arrested growth (LAGs) indicates periodic interruptions of growth, and likely expressed their ability to respond to rapid environmental changes. The fossil bones show post-mortem modifications such as weathering, fragmentation, abrasion and hydraulic sorting during transport. Diageneticprocesses include substitution, fracturing, plastic deformation due to lithostatic compression, and permineralization events. Petrographic and SeM-eDS analyses show the substitution of hydroxyapatite by fluorapatite in the bone microstructure. Permineralization stages include infilling of vascular canals, trabeculae and fractures with iron oxides and carbonate minerals during the burial history. This work provides an integral approach to the study of dinosaurs from the Loncoche Formation for assessing the diagenetic changes in the bone microstructure and its link with burial environments.